Performing Exile Foreign Bodies - Rudakoff, Judith (Intellect, 2017)
This book brings together essays by an international group of scholars and artists, focusing on live performance inspired by living in exile, or created by exiled artists. Bringing together a range of perspectives to examine the full impact of political, socio-economic or psychological experiences of exile, Performing Exile: Foreign Bodies presents an inclusive mix of established and emerging voices from varied cultural and geographic affiliations. Chapters blend close critical analysis and autoethnography to document and interrogate performances and the political, religious, economic and cultural contexts that inform them. With a foreword by Yana Meerzon, and featuring essays on artists of Mexican, Korean-American, Lebanese-Quebecois, Spanish, Azerbaijani and Canadian Aboriginal origin, to name a few, Performing Exile is truly diverse.